2010
DOI: 10.1096/fj.09-138198
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between progression of coronary artery disease and circulating endothelial progenitor cells

Abstract: The pathophysiology of coronary artery disease (CAD) progression is not well understood. Endothelial progenitor cells (EPCs) may have an important role. In the present observational cohort study we assessed the number of circulating EPCs in 136 patients undergoing elective percutaneous coronary intervention and who had at least one major epicardial vessel with a nonsignificant stenosis [<50% diameter stenosis (DS)], and the relationship between plasma EPC levels and the 24-mo progression of the nonsignificant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 46 publications
1
41
0
3
Order By: Relevance
“…[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Characteristics of studies included from meta-analysis are given in the Table. The most important reason whereby studies initially retrieved were finally excluded from meta-analysis was the lack of a poolable risk estimate and impossibility to calculate such estimate from the data provided (Online Table III). Pooled cumulative clinical characteristics of the metaanalyzed patient population are reported in Online Table IV.…”
Section: Overall Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Characteristics of studies included from meta-analysis are given in the Table. The most important reason whereby studies initially retrieved were finally excluded from meta-analysis was the lack of a poolable risk estimate and impossibility to calculate such estimate from the data provided (Online Table III). Pooled cumulative clinical characteristics of the metaanalyzed patient population are reported in Online Table IV.…”
Section: Overall Characteristics Of Included Studiesmentioning
confidence: 99%
“…Four of the 21 studies (n=512 patients, 12.8% of the total population) were conducted in patients with acute coronary syndrome, acute myocardial infarction, or stroke. 20,25,27,34 For the remainders, the underlying disease or condition was elective percutaneous intervention in 7 of 17 studies (n=795 patients; 19.1%), [17][18][19]22,29,31,33 elective coronary angiography for suspected coronary artery disease in 2 of 17 (n=1412 patients; 34.0%), 28,32 end-stage renal disease in 4 of 17 studies (n=705 patients; 17.0%), 23,24,26,35 chronic heart failure in 1 of 17 studies (n=156 patients; 3.8%), 16 and aortic stenosis in 1 of 17 study (n=261 patients; 6.3%). 35 One study included patients with and without chronic CVD at baseline, 21 and 1 study included both healthy subjects and patients with chronic or acute CVD.…”
Section: Overall Characteristics Of Included Studiesmentioning
confidence: 99%
“…Recruitment of BM-EPCs to the vascular lumen occurs after induction of cardiovascular stress (18), although the exact mechanism by which this occurs is not known. BM-EPCs are classified as early stage (2 days to 3 wk in culture after isolation from the bone marrow) at which point they resemble angiogenic monocytes or macrophages with low proliferation and capacity for enhancing tube formation or late stage (3)(4)(5)(6)(7)(8)(9)(10)(11)(12) wk in culture after isolation from the bone marrow) with a highly proliferative nature and ability to form tubes (18,54,55,59). However, BM-EPC identity and characterization are nontrivial and debated in the field (20).…”
mentioning
confidence: 99%
“…Since the proper markers to use for BM-EPCs are highly debated, it is very important to denote specific growth conditions, markers, and phenotypic characterizations used when classifying BM-EPCs. One hallmark of the CD34ϩ/VEGFR-2ϩ population of BM-EPCs is that they have been associated with coronary artery disease (7,18,62). Once in the vasculature, the relationship of this population of BMEPCs to neovascularization has been linked to enhanced antiapoptotic function through VEGF-A stimulation of VEGFR-2, increased nitric oxide (NO) release, and enhanced PI3K/AKT signaling (18,32,68).…”
mentioning
confidence: 99%
“…Some reports suggest that the number of CPCs determined by CFU-EC inversely correlates with the Framingham risk score, and a decrease in CPCs is used as a biological marker of vascular damage. 6, 13 It has also been suggested that CPCs characterized by CD34 + VEGFR2 + or CD133 + contribute to restoration of denuded endothelial cells and are a useful tool for predicting cardiovascular outcome in CAD patients. 7 In contrast, several reports suggest that CPCs defined as DiL-Ac-LDL/lectinpositive cells increase with the Framingham risk score.…”
Section: Article P 1929mentioning
confidence: 99%